2021
DOI: 10.3390/brainsci11060774
|View full text |Cite
|
Sign up to set email alerts
|

Autistic Traits and Attention-Deficit Hyperactivity Disorder Symptoms Predict the Severity of Internet Gaming Disorder in an Italian Adult Population

Abstract: Over the last decade, internet gaming has been a fast-growing recreational activity. Gamers risk their leisure activity becoming an addiction. In the present study, we aimed to measure the prevalence of Internet Gaming Disorder (IGD) in an adult population of video game players and to investigate the association between demographic variables, Autism Spectrum Disorder (ASD) traits, Attention-Deficit Hyperactivity Disorder (ADHD) severity, and IGD in adults. Through an online survey, we recruited 4260 individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 43 publications
0
13
1
Order By: Relevance
“…There is limited information on IGD locally during the pandemic period. A European study performed among the adult population during the pandemic showed that the prevalence of IGD was 29.6% [38], while a study in Japan discovered that there was 1.6 times increment of the prevalence, from 3.7% to 5.6% before and during pandemic [39]. In this study, we found that the prevalence of IGD was only 2.5%, which is the lowest among other countries [9,10,36,39].…”
Section: Discussioncontrasting
confidence: 49%
“…There is limited information on IGD locally during the pandemic period. A European study performed among the adult population during the pandemic showed that the prevalence of IGD was 29.6% [38], while a study in Japan discovered that there was 1.6 times increment of the prevalence, from 3.7% to 5.6% before and during pandemic [39]. In this study, we found that the prevalence of IGD was only 2.5%, which is the lowest among other countries [9,10,36,39].…”
Section: Discussioncontrasting
confidence: 49%
“…In terms of ADHD, in addition to a bidirectional relationship between IGD and ADHD (Vasilis , a unidirectional relationship from ADHD to IGD (Concerto et al, 2021;Vally, 2021) as well as from IGD to ADHD were found (B. Evren, C. Evren, E. Dalbudak, M. Topcu, & N. Kutlu, 2019) in regression analyses.…”
Section: Psychological Factors Associated With Igdmentioning
confidence: 99%
“…Although there is a strong link between problematic internet use and a wide range of mental issues such as anxiety/depression, substance abuse, poor sleep quality/insomnia and attention deficit hyperactivity disorder (ADHD), the association has not entirely been clarified as only cross-sectional studies exist [ 10 , 11 , 12 , 13 , 14 ]. However, recent studies have shown common vulnerability factors and bidirectional interactions between ADHD and gaming disorder, raising the possibility of the need for screening for this condition among problematic gamers and internet addicts [ 15 , 16 ]. Furthermore, depression and hopelessness were also found to be more common among gaming addicts in [ 17 ].…”
Section: Introductionmentioning
confidence: 99%